Femoral Neck Shaft Angle of Adult Bangladeshi Male (Bangladesh Journal of Anatomy, 2016)
Background: Femoral neck shaft angles (FNSAs) are an important measure for the assessment of hip and planning of operations in the upper part of femur. From a bio-mechanical standpoint bone geometryis are related to the body weight. Geometric parameters like the diameter of the femoral head and neck, the length of neck and the femoral neck shaft angle are determinant factors of osteoporotic patients. Objective: The study was carried out to measure the right and left femoral neck shaft angles from radiographs and to provide a base line data of femoral neck shaft angle of Bangladeshi adult male so that adequate planning and preoperative selection of orthopeadic implant for surgeries involving femoral neck can be taken. Materials and method: The study was a cross - sectional analytical type which involved measuring femoral neck shaft angles (FNSAs) of anterior posterior views of 25 male pelvis, showing the hip joint and proximal part of femur of both sides. Radiographs of adult male pelvis commented normal by the radiologist were taken as study materials. Femoral neck shaft angles (FNSAs) were measured by goniometer. Results: Male neck shaft angle of the femur (FNSAs) revealed that there were no significant difference in FNSAs between right and left side.Bangladesh Journal of Anatomy July 2016, Vol. 14, No. 2 pp. 36-38